2013
DOI: 10.1002/ar.22741
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Transglutaminase 6 in the Central Nervous System of Adult Mice

Abstract: Our previous study identified a new form of spinocerebellar ataxia (SCA), in which mutations in the gene coding for transglutaminase 6 (TG6) were suggested to be causative. However, the data concerning cellular distribution of TG6 in the brain is still fragmentary. Therefore, we now report a comprehensive immunohistochemical examination of the expression profile of TG6 in adult mouse brain. TG6 was abundantly expressed in the septal region, basal ganglia, hypothalamus and brainstem. Notably, numerous TG6-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
(26 reference statements)
2
10
0
Order By: Relevance
“…Our results are supported by Caputo and coworkers which observed that prolonged treatment of human intestinal Caco-2 cell line (extensively used as a model of the intestinal barrier) with p31-43 increased TG2 protein expression, indicating a non-tissue-specific post-translational mechanism of the gliadin peptide 31-43 24 . Furthermore, it has been shown that TG6 immunoreactivity is present in the CA3 region, but not in CA1/CA2 or in the dentate gyrus (DG) 25 thus supporting our in vitro results in which we observed that p31-43 exacerbates kainate neurotoxicity selectively in the CA3 region of hippocampal slices. Hence, we tested the non-selective TGs inhibitor Z-DON-Val-Pro-Leu-OMe (Z-DON) 26 as a possible neuroprotective drug in our system.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are supported by Caputo and coworkers which observed that prolonged treatment of human intestinal Caco-2 cell line (extensively used as a model of the intestinal barrier) with p31-43 increased TG2 protein expression, indicating a non-tissue-specific post-translational mechanism of the gliadin peptide 31-43 24 . Furthermore, it has been shown that TG6 immunoreactivity is present in the CA3 region, but not in CA1/CA2 or in the dentate gyrus (DG) 25 thus supporting our in vitro results in which we observed that p31-43 exacerbates kainate neurotoxicity selectively in the CA3 region of hippocampal slices. Hence, we tested the non-selective TGs inhibitor Z-DON-Val-Pro-Leu-OMe (Z-DON) 26 as a possible neuroprotective drug in our system.…”
Section: Discussionsupporting
confidence: 92%
“…TG6 is expressed in a subset of neurons in the cerebellar cortex (Purkinje cells) and cerebellar nuclei, but also in the thalamus. 13,14 The thalamus is involved in motor control in terms of acting as a relay center between the cerebellum and the motor cortex. 15 The observed significant thalamic atrophy and tendency toward cerebellar atrophy are therefore in line with loss or impairment of TG6þ neurons, potentially affecting GABA-ergic inhibitory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…26 In adult mice, TG6 is primarily and abundantly expressed in neurons across the central nervous system, including spinal motor neurons, and TG6 expression is associated with neurogenesis during central nervous system development and in regions associated with motor function. 13,27 The gene encoding TG6 (TGM6; NM_198994 and NM_001254734) has recently been identified as a novel causative gene of one form of spinocerebellar ataxia. 28,29 Taken together, these findings provide increasing evidence that TG6 may play an important role in motor control and that autoantibodies to TG6 might interfere with its action and be involved in the pathogenesis of neurodegenerative diseases.…”
Section: Role Of Tg6 Autoantibodies In the Neuronal Damage In Alsmentioning
confidence: 99%
“…12 Tissue transglutaminase 6 is primarily expressed in the brain. 13 The prevalence of TG6 antibodies (IgA and/or IgG) was reported in 62% of patients with gluten ataxia and in 45% of those with CD without neurologic manifestations. 12 The TG6 antibodies are sensitive and specific in gluten ataxia.…”
mentioning
confidence: 97%